Eclosion and adult longevity traits of Rhagoletis tabellaria (Diptera: Tephritidae) and Utetes tabellariae (Hymenoptera: Braconidae) in the laboratory. Issue 2 (15th April 2020) - Yee, W.L.; Forbes, A.A.; Feder, J.L.
Abstract: Eclosion times and rates of Rhagoletis tabellaria (Fitch) (Diptera: Tephritidae) and its parasitoid wasp Utetes tabellariae (Fischer) (Hymenoptera: Braconidae) held at different chilling durations were determined in the laboratory. Adult fly and wasp longevity were also determined. Adult female and male flies from R. tabellaria puparia chilled for 195 days at 4.8 °C and then held at 23.2 °C eclosed on average earlier than U. tabellariae reared from R. tabellaria puparia. Rhagoletis tabellaria also eclosed significantly earlier from puparia chilled for 150 days than 120 days at 2.7 °C, but U. tabellariae eclosion from the two treatments did not differ significantly. Rhagoletis tabellaria eclosion rates were greater with longer chill durations, but U. tabellariae eclosion rates per R. tabellaria puparium did not differ among chill durations. No R. tabellaria eclosed from nonchilled puparia held at 20–22 °C, but at least 18.8% of nonchilled U. tabellariae eclosed. Female and male R. tabellaria on average survived 52.1 and 83.3 days, respectively, while female and male U. tabellariae survived 37.7 and 28.7 days, respectively. Results indicate diapause and developmental traits of R. tabellaria may be more dependent on chilling durations and less flexible than those of U. tabellariae, a wasp that appears adapted to flies in the R. tabellaria species complex.